IgG4-Related Disease: Mimickers and Diagnostic Pitfalls. Issue 2 (March 2022) - Martín-Nares, Eduardo; Hernández-Molina, Gabriela; Baenas, Diego Federico; Paira, Sergio
Abstract : Background: The tendency of IgG4-related disease (IgG4-RD) to form pseudotumors, as well as its multisystemic nature, makes it the perfect mimicker of many conditions. Moreover, some clinical, serological, radiological, or histological features of the disease might be shared with some mimickers. Recently, 4 clinical phenotypes have been identified, and patients grouped in each phenotype have distinctive demographic, clinical, and serological features and outcomes, and, as expected, for each phenotype, a set of differential diagnoses should be considered. Summary of the Literature: The main differential diagnoses for the pancreato-hepato-biliary phenotype are pancreatic adenocarcinoma and cholangiocarcinoma. Other differential diagnoses include type 2 autoimmune pancreatitis and primary sclerosing cholangitis. In patients with retroperitoneal/aortic phenotype, inflammatory conditions such as idiopathic retroperitoneal fibrosis and large vessel vasculitides should be ruled out, and most of the time, a biopsy will be needed to exclude malignancies. In head and neck limited phenotype, autoimmune conditions (eg, granulomatosis with polyangiitis, Graves orbitopathy, sarcoidosis), malignancies, and histiocytosis should be ruled out, whereas the main differential diagnoses of the Mikulicz/systemic phenotype are Sjögren syndrome, granulomatosis with polyangiitis, and multicentric Castleman disease. Conclusions: Approaching a patient with probable IgG4-RD through a clinical phenotype framework will ease the diagnostic algorithm and facilitate the prompt recognition of the disease. There are certain clinical, serological, radiological, and histological features in each clinical phenotype that, if present, increase the likelihood that a patient may have IgG4-RD instead of the mimicker condition. Those clues that point toward IgG4-RD diagnosis should be actively sought in the workup of patients.